2003
DOI: 10.1038/sj.bmt.1704210
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacterial infections in Chinese hematopoietic stem cell transplantation recipients

Abstract: Between 1995 and 2002, nine cases of nontuberculous mycobacterium (NTM) were isolated from 462 allogeneic stem cell transplant (SCT) recipients (1.9%), and none from 139 autologous cases. They included three cases each of Mycobacterium fortuitum and M. chelonae, and single cases of M. scrofalaceum, M. gordonnae and M. avium complex. Seven cases were respiratory, including five cases requiring treatment, and two involved infected catheters and vascular conduits. Compared with nine cases of mycobacterium tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Further largescale studies of the outcome of NTM infection in hematological patients are warranted [19]. Au et al reported that NTM isolation is a marker for severe immunosuppression and poor prognosis in hematological transplant recipients [8]. Our study also showed that patients who received allogeneic hematopoietic stem cell transplantation were at increased risk of developing NTM infection.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Further largescale studies of the outcome of NTM infection in hematological patients are warranted [19]. Au et al reported that NTM isolation is a marker for severe immunosuppression and poor prognosis in hematological transplant recipients [8]. Our study also showed that patients who received allogeneic hematopoietic stem cell transplantation were at increased risk of developing NTM infection.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, we showed that the mean prevalence was 1.2% in patients with hematological malignancy, and that it ranged from 0.3% in patients with myeloma to 3.8% in patients with chronic lymphoid leukemia. The incidence of NTM infection among hematopoietic stem cell recipients ranged from 0.4% to 4.9% noted in previous studies [7][8][9][10]. Compared with the general population [3][4][5][6], patients with hematological malignancy have a significantly higher risk of In this study, rapidly growing mycobacteria (M. abscessus, M. fortuitum, M chelonae, 42%) were the most common isolates, followed by MAC (38%) and M. kansasii (18%).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These authors suggested some possible causes of the association: (1) management with multiple antibiotics before the diagnosis, which could predispose to the growth of fungus rather than bacteria; (2) a common host defense abnormality; (3) steroid therapy; or (4) immunosuppression. A previous study of NTM infection in SCT recipients also demonstrated that coinfection with aspergillus was common [14]. In the current study, 10 out of 25 patients in whom NTM was isolated from respiratory specimens had simultaneous aspergillus infection, and five out of these 10 patients died.…”
Section: Discussionmentioning
confidence: 72%
“…Optimum treatment duration is not defined, but infection is most frequently treated for 12–18 months. M chelonae is frequently reported as causing infection in patients with cystic fibrosis,24 erythroleukaemia,5 chronic lymphocytic leukaemia6 and paediatric acute non-lymphoblastic leukaemia,7 and in haematopoietic stem cell transplantation recipients8 (including catheter related infection),9 , 10 cord blood stem cell transplantation recipients11 and allogeneic bone marrow transplantation recipients 12. It has also frequently been reported to cause fever in neutropenic patients 13.…”
Section: Discussionmentioning
confidence: 99%